The influence of board characteristics and ownership structure on integrated reporting: the moderating role of firm size - Radin, Rima; Tahir, Nor Suziwana; Othman, Sarina (2023)
Integrated reporting (IR) is the futuristic reporting approach that provides a company’s value creation over time. It assists stakeholders, particularly investors to assess the firm’s prospects to make an informed decision. Currently, IR has gained attention among academics and practitioners. However, studies on the determinants of the IR disclosure level are still limited, especially from the voluntary setting and emerging markets like Malaysia. This study aims to fill this literature gap by examining the role of board characteristics and ownership structure on IR and the moderating role of firm size among Malaysian public listed companies. It combines the legitimacy theory and agency theory to analyze a sample of 48 observations over the period 2018 to 2020. The results indicate that firm size moderates the significant relationship between board education and IR disclosure level. The findings have significant implications for companies to include board educational level as part of the board diversity’s objective and providing the financial and incentives to steer the company’s IR strategy. The findings also have important implications for regulators to extend the board diversity regulation to educational level. Besides, they can also develop a conducive mechanism which consists of policy and clear guidelines, an appropriate standard, aspect of financing and sufficient incentives, as well as increase the awareness and knowledge on IR practices. This study, therefore, contributes to the determinants of IR and the corporate reporting development in Malaysia.